Palm raceme as a promising biomass precursor for activated carbon to promote lipase activity with the aid of eutectic solvents - M. Abed, Khalid; Hayyan, Adeeb; Elgharbawy, Amal A. M.; F. Hizaddin, Hanee; Hashim, Mohd Ali; Abu Hasan, Hassimi; Hamid, Mahar Diana; M. Zuki, Fathiah; Saleh, Jehad; GH Aldaihani, Ahmad (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
This study concerns the role of activated carbon (AC) from palm raceme as a support material for the enhancement of lipase-catalyzed reactions in an aqueous solution, with deep eutectic solvent (DES) as a co-solvent. The effects of carbonization temperature, impregnation ratio, and carbonization time on lipase activity were studied. The activities of Amano lipase from Burkholderia cepacia (AML) and lipase from the porcine pancreas (PPL) were used to investigate the optimum conditions for AC preparation. The results showed that AC has more interaction with PPL and effectively provides greater enzymatic activity compared with AML. The optimum treatment conditions of AC samples that yield the highest enzymatic activity were 0.5 (NaOH (g)/palm raceme (g)), 150 min, and a carbonization temperature of 400 °C. DES was prepared from alanine/sodium hydroxide and used with AC for the further enhancement of enzymatic activity. Kinetic studies demonstrated that the activity of PPL was enhanced with the immobilization of AC in a DES medium.